2021
DOI: 10.3390/pathogens10040434
|View full text |Cite
|
Sign up to set email alerts
|

Role of the β-Catenin/REG Iα Axis in the Proliferation of Sessile Serrated Adenoma/Polyps Associated with Fusobacterium nucleatum

Abstract: Although sessile serrated adenoma/polyps (SSA/Ps) may arise through a pathway different from the traditional adenoma–carcinoma sequence, details of SSA/P tumorigenesis still remain unclear. Fusobacterium nucleatum (Fn) is frequently detected in colorectal cancer (CRC) tissues and may play a pivotal role in colorectal carcinogenesis. Here, we investigated the relationship between Fn and the β-catenin/REG Iα axis in SSA/Ps and their involvement in the proliferation of these lesions. Fn was detected in SSA/Ps by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Gut microbiota dysregulation may precipitate intestinal epithelial cell dysfunction and mucosal damage, instigating intestinal inflammation. Moreover, alterations in the gut microbiota alterations may potentiate colitis-related tumorigenesis through the perpetuation of chronic inflammation and the production of carcinogens [ [ 35 ]]. Existing literature suggests that rutin can palliate DSS-induced colonic inflammation in mice by impeding the production and activation of inflammatory mediators, modulating immune cell activity and cytokine secretion, and bolstering the intestinal mucosal barrier to mitigate intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota dysregulation may precipitate intestinal epithelial cell dysfunction and mucosal damage, instigating intestinal inflammation. Moreover, alterations in the gut microbiota alterations may potentiate colitis-related tumorigenesis through the perpetuation of chronic inflammation and the production of carcinogens [ [ 35 ]]. Existing literature suggests that rutin can palliate DSS-induced colonic inflammation in mice by impeding the production and activation of inflammatory mediators, modulating immune cell activity and cytokine secretion, and bolstering the intestinal mucosal barrier to mitigate intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum modifies colonic Th17 cell frequency and IL-17 expression recombinant free fatty acid receptor 2 (FFAR2)-dependently ( Brennan et al., 2021 ). Moreover, it positively correlated with the expression of Wnt-β-catenin (activated by FadA─E-cadherin) and REG Iα signaling, both of which effectively promotes the proliferation of sessile serrated adenoma/polyp ( Rubinstein et al., 2013 ; Nishimura et al., 2021 ). ENO1 gene and ANGPTL4 protein enhance the high glycolysis of colorectal cancer cells, and these two regulatory mechanisms could be upregulated by F. nucleatum either, which further support F. nucleatum colonization and positively collated with poor prognosis ( Hong et al., 2021 ; Zheng et al., 2021 ).…”
Section: Mechanisms Of Oral Microbiome Affecting Intestinal Microbiotamentioning
confidence: 99%
“…Recent evidence has also confirmed that fusobacteria are able to reach metastases from the primary tumour or from the oral cavity mainly via the circulatory system rather than the gastrointestinal tract [44]. Nishimura et al demonstrated that Fn might play a role in the proliferation of sessile serrated adenoma/polyp through promoting the β-catenin nuclear translocation and regenerating gene (REG) Iα overexpression [45]. REG is a family of proteins that have a cellular proliferative and antiapoptotic effect on inflamed or neoplastic lesions of the gastrointestinal tract [46].…”
Section: Colorectal Cancer and Fusobacterium Nucleatum Pathogenic Mec...mentioning
confidence: 99%